1997
DOI: 10.1093/ajcp/108.6.662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti–Factor Xa Heparin Activity and Activated Partial Thromboplastin Time in 2,773 Plasma Samples From Unfractionated Heparin–Treated Patients

Abstract: C o m p a r i s o n o f A n t i -F a c t o r X a H e p a r i n A c t i v i t y a n dA c t i v a t e d P a r t i a l T h r o m b o p l a s t i n T i m e i n 2 , 7 7 3 P l a s m a S a m p l e s F r o m U n f r a c t i o n a t e d H e p a r i n -T r e a t e d P a t i e n t s TERRY K. ROSBOROUGH, MDThis study was conducted to evaluate two methods of determining the "therapeutic range" of the activated partial thromboplastin time (APTT) during unfractionated heparin treatment. Multiple fresh plasma samples from 694… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Between 30 and 60 samples have been used in some studies employing linear regression analysis (Brill-Edwards et al, 1993;. However, linear regression analysis on a relatively small number of samples does not necessarily yield the same results as a large sample would, as indicated in a study comparing APTT and anti-Xa activity in more than 2700 samples (Rosborough, 1997). This study suggested that at least several hundred samples may be required.…”
Section: Therapeutic Ranges Specific For Aptt Techniquementioning
confidence: 99%
“…Between 30 and 60 samples have been used in some studies employing linear regression analysis (Brill-Edwards et al, 1993;. However, linear regression analysis on a relatively small number of samples does not necessarily yield the same results as a large sample would, as indicated in a study comparing APTT and anti-Xa activity in more than 2700 samples (Rosborough, 1997). This study suggested that at least several hundred samples may be required.…”
Section: Therapeutic Ranges Specific For Aptt Techniquementioning
confidence: 99%
“…14 When these results with lot SA-224B were subsequently compared by analysis of agreement with lot SA-239C, 1 of the 2 lots used in this study, it was found that lot SA-239C produced values that were 3.5% higher than those obtained with lot SA-224B. Accordingly, the therapeutic range for UH therapy was adjusted upward to 62 to 88 seconds.…”
Section: Resultsmentioning
confidence: 78%
“…However, in other data sets, particularly when outlier data are more frequent, the differences between the methods can be more important. [12][13][14] When the Bland and Altman 12 method was applied to the data in this study, it showed that the bias was for the newer APTT reagent lot to produce values 88.9% of those obtained with the older reagent lot. This meant that the upper limit of normal for the APTT needed to be lowered by about 11%, and the APTT UH therapeutic range needed to be lowered by the same proportion.…”
Section: Discussionmentioning
confidence: 99%
“…, the generally accepted criterion standard for the therapeutic range for heparin, corresponds to APTT ratios of between 1.6 and 2.7 to 3.7 and 6.2 times control with different reagents [11][12][13][14][15]. Therefore, the use of a ÔstandardÕ APTT therapeutic range of 1.5-2.5 for all reagents would be expected to lead to systematic administration of subtherapeutic doses of heparin in many hospitals.…”
Section: Heparin Monitoringmentioning
confidence: 99%